Characteristics of Fish Catched by Drift Gillnet in Tanjung Solok Kuala Jambi Tanjung Jabung Timur - Kurniasih, Novtia; Nurhayati, Nurhayati; Sumadja, Wiwaha Anas (Jurnal Perikanan dan Kelautan, 2021)
Tanjung Solok sub-district is one of the areas in Kuala Jambi which is the landing location for fish. One of the most widely used fishing gear to catch fish is drift gillnets. This study aims to observe the characteristics of fish catches with drift gill nets landed in the Tanjung Solok sub-district. The analysis was carried out descriptively with survey data collection methods and random sampling. The gill mesh used is 4 inches in size. Data collection was carried out on 12 ships with 10 repetitions. The catches that were obtained were threadfin, white pomfret, black pomfret, mackerel, conger eel, flatfish, and dorab wolf-herring with the most catch was 1,143 black pomfret and the smallest catch was 75 conger eel. The diversity index of 1.66 is included in the medium category, while the dominance index is 0.24 in the low category. The length of each fish varies. Based on the research it can be concluded that the characteristics of catches by fish size shows that measure decent overall catch more than 30% and 70% are still in decent size has not been caught